PERAN KEPEMIMPINAN KEPALA SEKOLAH DALAM PENGUATAN MUTU PEMBELAJARAN MELALUI SUPERVISI AKADEMIK BERBASIS DATA DI SEKOLAH DASAR - Fatimah, Hana; Utami, Fajar Sri; Muhibbin, Ahmad; Sutopo, Anam (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study is motivated by the suboptimal use of academic supervision data as the basis for evaluating learning processes. The study aim to describe the role of the principal’s leadership in strengthening learning quality through data-based academic supervision at MI Muhammadiyah Tahfidzul Qur’an, Matesih, Karanganyar. The study focuses on three main aspects: the form of the principal’s leadership in implementing academic supervision, the implementation of data-based academic supervision, and its contribution to strengthening learning quality. The research adopts a descriptive qualitative design with teachers and the school principal as the research subjects. Data were collected through in-depth interviews, participatory observations, and documentation, while data analysis used the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The validity of the data was ensured through source and technique triangulation. The findings reveal that the principal applied transformational and participatory leadership styles that fostered a collaborative and reflective culture among teachers. Data-based academic supervision was systematically implemented by utilizing classroom observation results, learning evaluations, and teacher reflections as the basis for professional development. The application of data-based supervision improved the objectivity of assessments, teacher professionalism, learning effectiveness, and student achievement. The study concludes that the integration of principal leadership with data-based academic supervision serves as an effective strategy to build a sustainable culture of learning quality in elementary education. The implications indicate that improving the quality of learning in elementary schools can be achieved more effectively when principals develop a structured, data-driven, and reflective academic supervision system. The findings of this study can serve as a reference for principals and school supervisors in designing continuous professional development policies for teachers, as well as a basis for future researchers to explore data-based academic supervision models in broader educational contexts.